1994
DOI: 10.1039/c39940002129
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of poly(pyrrole)–silica–magnetite nanocomposite particles

Abstract: UKBN? 9QJPyrrole is polymerised in the presence of ultrafine silica-coated magnetite particles; the resulting colloidal poly(pyrro1e)-silica-magnetite nanocomposites have a conducting polymer content of 75 mass% and exhibit superparamagnetism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 12 publications
1
15
0
Order By: Relevance
“…Infrared spectra were recorded on a Perkin-Elmer FT 1710 spectrometer in CHCl 3 as solvent. 1 High resolution mass spectra were taken on a VG Autospec instrument.…”
Section: Methodsmentioning
confidence: 99%
“…Infrared spectra were recorded on a Perkin-Elmer FT 1710 spectrometer in CHCl 3 as solvent. 1 High resolution mass spectra were taken on a VG Autospec instrument.…”
Section: Methodsmentioning
confidence: 99%
“…Several potential applications were suggested for polypyrrole--silica nanocomposite particles, including their use as highly coloured marker particles for immunodiagnostic assays 21 and as new synthetic mimics for understanding the behaviour of silicate-based micro-meteorites. 8,9 However, such syntheses suffer from the following disadvantages: (i) they must be conducted in moderately acidic solution (pH 0 to 2) to obtain highly conjugated conducting polymer chains; (ii) due to their highly exothermic nature, they are typically limited to rather low monomer concentrations (typically only 1--3% w/v ); (iii) the reaction solutions are always heavily contaminated with both excess silica sol and spent oxidant salts and hence require time-consuming purification via multiple centrifugation/ redispersion cycles.…”
Section: Steven P: Armesmentioning
confidence: 99%
“…These nanocomposites often behave like semiconductors in the temperature range of 235-340 K. Other reports can be found in Another field of interest is polymerglass nanocomposites. 106 Hwang et al 107 reported the potential use of NiO-Ni(OH) 2 nanocomposites as humidity sensors, though the mechanism of humidity sensors by this kind of material is not completely understood at present.…”
Section: Electrical Propertiesmentioning
confidence: 99%